Antibody Afucosylation Augments CD16-Mediated Serial Killing and IFNγ Secretion by Human Natural Killer Cells - Karampatzakis, Alexandros; Brož, Petr; Rey, Camille; Önfelt, Björn; Cruz De Matos, Gabriela Dos Santos; Rycroft, Daniel; Ambrose, Ashley; Davis, Daniel M. (Frontiers in Immunology, 2021)
One mechanism by which monoclonal antibodies (mAb) help treat cancer or autoimmune disease is through triggering antibody-dependent cellular cytotoxicity (ADCC) via CD16 on Natural Killer (NK) cells. Afucosylation is known to increase the affinity of mAbs for CD16 on NK cells and here, we set out to assess how mAb afucosylation affects the dynamics of NK cell interactions, receptor expression and effector functions. An IgG1 version of a clinically important anti-CD20 mAb was compared to its afucosylated counterpart (anti-CD20-AF). Opsonization of CD20-expressing target cells, 721.221 or Daudi, with anti-CD20-AF increased NK cell cytotoxicity and IFNγ secretion, compared to anti-CD20. The afucosylated mAb also caused a more rapid and greater loss of CD16 from NK cell surfaces. Loss of CD16 has recently been shown to be important for NK cell detachment and sequential engagement of multiple target cells. Here, live-cell time-lapse microscopy of individual cell-cell interactions in an aqueous environment and a three-dimensional matrix, revealed that anti-CD20-AF induced more rapid killing of opsonized target cells. In addition, NK cells detached more quickly from target cells opsonized with anti-CD20-AF compared to anti-CD20, which increased engagement of multiple targets and enabled a greater proportion of NK cells to perform serial killing. Inhibition of CD16 shedding with TAPI-0 led to reduced detachment and serial killing. Thus, disassembly of the immune synapse caused by loss of cell surface CD16 is a factor determining the efficiency of ADCC and antibody afucosylation alters the dynamics of intercellular interactions to boost serial killing.